2021
DOI: 10.1159/000514931
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Intervention for Overweight/Obese Pregnant Women with Polycystic Ovarian Syndrome: Lessons and Challenges

Abstract: <b><i>Introduction and Objective:</i></b> Polycystic ovary syndrome (PCOS) is the most common reproductive disorder in women of reproductive age, and overweight and obesity are highly prevalent in women with PCOS. This study aims to explore whether lifestyle intervention can improve gestational weight gain (GWG), glucolipid metabolism, and perinatal outcomes in overweight/obese pregnant women with PCOS. <b><i>Methods:</i></b> This study is a randomized controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…15 Similarly, the few lifestyle weight loss interventions initiated after pregnancy also observed little or no change in lipid profiles. [28][29][30][31][32] Nonetheless, our finding of the lipidlowering effect of maternal weight loss prior to pregnancy was consistent with an animal study, which reported that preconception dietary restriction in obese mice led to decreased cholesterol and LDL-C levels in gestation. 33 The downtrend in levels of total cholesterol and LDL-C was accompanied by a parallel reduction in HDL-C levels, which is an unexpected finding as weight loss has historically been associated with improved HDL-C thus ameliorated cardiovascular risks.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…15 Similarly, the few lifestyle weight loss interventions initiated after pregnancy also observed little or no change in lipid profiles. [28][29][30][31][32] Nonetheless, our finding of the lipidlowering effect of maternal weight loss prior to pregnancy was consistent with an animal study, which reported that preconception dietary restriction in obese mice led to decreased cholesterol and LDL-C levels in gestation. 33 The downtrend in levels of total cholesterol and LDL-C was accompanied by a parallel reduction in HDL-C levels, which is an unexpected finding as weight loss has historically been associated with improved HDL-C thus ameliorated cardiovascular risks.…”
Section: Discussionsupporting
confidence: 90%
“…Albeit a larger amount of weight loss in the intervention group, there was no between‐group difference in levels of triglycerides at 14 weeks' gestation 15 . Similarly, the few lifestyle weight loss interventions initiated after pregnancy also observed little or no change in lipid profiles 28–32 . Nonetheless, our finding of the lipid‐lowering effect of maternal weight loss prior to pregnancy was consistent with an animal study, which reported that preconception dietary restriction in obese mice led to decreased cholesterol and LDL‐C levels in gestation 33 …”
Section: Discussionsupporting
confidence: 85%
“…It may be observed that it is common to provide lifestyle interventions, inclusive of nutrition and exercise, for changes in lifestyle for overweight and obese women. In overweight or obese pregnant women, lifestyle interventions were effective in the maintenance of stable weight gain and the control of fatigue and pregnancy stress [ 18 ], and were also effective in the reduction of weight and improvement of lipid levels [ 19 ]. In overweight and obese middle-aged women, it was effective in the increasing of health-promoting behaviors, reduction of psychological distress, weight loss, improvement of reproductive system symptoms [ 20 ], and increase in the pregnancy rate of obese and infertile women [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, non-pharmacological interventions in PCOS are an extensive research field, but we only focus on lifestyle interventions, acupuncture therapies and nutritional supplements, 11 which may lead to limitations of clinical practice. Second, considering that overweight/obese patients have an increased risk of metabolic disorders 32 and tend to benefit more from non-pharmacological interventions compared with normal weight patients, we will restrict the population to overweight/obese PCOS, which may limit the extrapolation of the conclusion. Third, the efficacy of different protocols of the same non-pharmacological intervention will not be investigated.…”
Section: Discussionmentioning
confidence: 99%